Regulatory Role of OsMADS34 in the Determination of Glumes Fate, Grain Yield, and Quality in Rice - Ren, Deyong; Rao, Yuchun; Leng, Yujia; Li, Zizhuang; Xu, Qiankun; Wu, Liwen; Qiu, Zhennan; Xue, Dawei; Zeng, Dali; Hu, Jiang; Zhang, Guangheng; Zhu, Li; et al. (Frontiers in Plant Science, 2016)
Grasses produce seeds on spikelets, a unique type of inflorescence. Despite the importance of grass crops for food, the genetic mechanisms that control spikelet development remain poorly understood. In this study, we used m34-z, a new mutant allele of the rice (Oryza sativa) E-class gene OsMADS34, to examine OsMADS34 function in determining the identities of glumes (rudimentary glume and sterile lemma) and grain size. In the m34-z mutant, both the rudimentary glume and sterile lemma were homeotically converted to the lemma-like organ and acquired the lemma identity, suggesting that OsMADS34 plays important roles in the development of glumes. In the m34-z mutant, most of the grains from the secondary panicle branches (spb) were decreased in size, compared with grains from wild-type, but no differences were observed in the grains from the primary panicle branches. The amylose content and gel consistency, and a seed-setting rate from the spb were reduced in the m34-z mutant. Interesting, transcriptional activity analysis revealed that OsMADS34 protein was a transcription repressor and it may influence grain yield by suppressing the expressions of BG1, GW8, GW2, and GL7 in the m34-z mutant. These findings revealed that OsMADS34 largely affects grain yield by affecting the size of grains from the secondary branches.